Physical and Chemical Aspects of Oil Agglomeration as a Method for Preparing Salty Coal for Thermal Processing - Shendrik, T. G.; Biletskyi, V. S.; Desna, N. A. (VÚRUP, 2025)
The article presents the results of coal-oil agglomeration of salty coal (SC) and examines how the properties of its components – coal and M100 mazut – impact the process. The research employed methods such as X-ray phase analysis (XPA), electron paramagnetic resonance (EPR), infrared (IR) spectroscopy, and functional chemical analysis. The study was found that oil agglomeration of salty coal not only changes technical characteristics (reducing ash content, salinity, and moisture) but also involves several physical and chemical interactions between the active centres of coal organic matter (COM) and the oil agent. EPR analysis revealed that the paramagnetic centre content (PMC) in the agglomerate was significantly lower than in its precursor components. This indicates a sharp shift in the intermolecular interactions within the system. X-ray diffraction results showed structural changes in the coal, noticeable even with just 5% mazut content in the raw material. The coal agglomerate, with around 30% mazut, displayed an increase in the proportion of non-aromatic polynaphthenic) fragments in the overall agglomerate structure (~70% compared to ~48% in the raw coal) and greater structural ordering (the h/l ratio doubled). IR spectroscopy and functional analysis showed that the concentration of quinone structures on the surface of the coal grains in the agglomerated products was lower than in the original samples, suggesting the direct reactivity of quinones in the process. Additionally, the active involvement of product’s organic matter thio- or ether bonds in the formation of coal-oil aggregates is also possible. Comparative studies of changes in band intensity and position in the IR spectra confirmed this conclusion. EPR data further suggest that RO2⋅ or RS2⋅ radicals are likely involved in the recombination reactions of coal and oil agent PMCs. Pyrolysis tests of salty coal, its mixture with mazut, and the coal-oil agglomerate showed that oil agglomeration significantly influences the thermolysis results. Pyrolysis of agglomerated coal demonstrated an additive increase in the organic matter conversion rate, as clearly seen from the yields of gaseous products and tar. These findings suggest that oil agglomeration is a promising method for preparing salty coal for thermal processing.
Фізико-хімічні аспекти нафтової агломерації як методу підготовки солоного вугілля до термічної переробки
Keywords: salty coal; oil agglomeration; XPA; IR spectroscopy; pyrolysis; EPR